Evaluation of soils of Jalgaon district of Maharashtra for cotton (Gossypium hirsutum) cultivation - SIDHU, G S; KANDPAL, B K; MANDAL, C (The Indian Journal of Agricultural Sciences, 2013)
Major soils of Jalgaon District of Maharashtra were evaluated for their suitability for cotton (Gossypium hirsutum L.) cultivation and their irrigation requirement. Umarti soil series was found permanently unsuitable (N2ts) while Lasur and Pimpri series were rated as presently unsuitable (N1tS). Bodvad and Bhod series were marginally suitable (S3s) for cotton, while Hingona, Bhava and Dhupa series Were evaluated as moderately suitable (S2ts and S2t). Slope, soil depth and coarse fragments were the major determining parameters for suitability class. Net irrigation water requirement of different soils was varied between 142-255 mm based on soil depth, plant available water capacity and length of growing period